Sportowe pasje kobiet. Przyczynek do jakościowych badań nad zawartością treści w prasie regionalnej i lokalnej Wielkopolski oraz jej pogranicza - Jurga-Wosik, Ewa (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Studies into the content of the local and regional press expand our knowledge about the life of local communities. The author limits herself to studying the narrow issue of women’s sporting interests, whereby she analyzes their active (as athletes and trainers) and passive (administering various sports, as fans) participation in amateur and professional sport. The paper also indicates which factors are decisive for the domination of a given sport in a region and considers to what extent the picture presented is true, reflects reality and exhausts all aspects of women’s interest in sport. The way in which press materials are presented is also interesting and confirms the observation that local and regional media have become tabloidized to a greater or lesser degree (depending on the type of periodical). The qualitative study has shown that women’s need to practice sport is not only an expression of their emancipation, a development of their skills, and a desire to break records, but at present it has primarily become a way of living a ‘healthy life’. The local and regional press fulfill two roles in this regard: they provide a wider presentation of professional and amateur sport and, to a lesser degree, persuade their readers to practice sport themselves (propagating a ‘healthy lifestyle’ accounts for an average of two articles out of eighteen qualified as ‘sport articles’). The research field encompassed a wide range of female sporting passions, while the examples discussed confirm that women live active lives.